Is the curriculum of transfusion medicine in MBBS aligned with practical needs: A point of view of fresh graduates - Umera Saleem; Muhammad Asif Naveed; Muhammad Samiullah; Urwah Tanveer; Shahroz Alam; Ahmed Faraz Zafar; Sohail Safdar (Asian Journal of Transfusion Science)
OBJECTIVE: The objective of the study is to assess the satisfaction level of doctors regarding their competence in the blood transfusion process and their reflection on training at the undergraduate level. BACKGROUND: Transfusion errors due to suboptimal knowledge and lack of training can lead to grave outcomes. Therefore, to optimize patient care, a thorough understanding of transfusion medicine basics is highly imperative for all medical graduates. METHODOLOGY: This survey was conducted online through Google forms with a questionnaire consisting of 15 questions. 8 medical colleges (4 government and 4 private) were selected by random cluster sampling technique. Data were analyzed with SPSS version 23. RESULTS: Of 502 participants, 53.8% were females and 69.9% were graduates of public medical colleges. About 84.6% did not receive any formal training on transfusion during graduation. Almost 82% felt that the current curriculum is not designed to meet their practical needs of blood transfusion and 52% agreed that knowledge of transfusion medicine is required for undergraduates. The survey also revealed that 70.5% of participants believed that whole blood is required for most patients and 49.8% did not feel confident to manage transfusion-related complications by themselves. CONCLUSION: Our survey showed that our undergraduate curriculum is not aligned with the practical transfusion needs of a young doctor. As transfusions are being carried out by these young doctors, this needs to be addressed by revising the current curriculum and incorporating teaching and hands-on training to our medical graduates.